Partially observable game-theoretic agent programming in Golog - Finzi, A; Lukasiewicz, T (Elsevier, 2020)
In this paper, we present the agent programming language POGTGolog (Partially Observable Game-Theoretic Golog), which integrates explicit agent programming in Golog with game-theoretic multi-agent planning in partially observable stochastic games. In this framework, we assume one team of cooperative agents acting under partial observability, where the agents may also have different initial belief states and not necessarily the same rewards. POGTGolog allows for specifying a partial control program in a high-level logical language, which is then completed by an interpreter in an optimal way. To this end, we define a formal semantics of POGTGolog programs in terms of Nash equilibria, and we then specify a POGTGolog interpreter that computes one of these Nash equilibria.